Analysis of soil quality in various land uses in the Central Rembangan micro-watershed, Indonesia - Hermiyanto, Bambang; Budiman, Subhan Arif; Basuki, Basuki; Hafizh, Muhammad; Maharani, Marcellia; Hadi, Syamsul (Brawijaya University, 2026)
Land degradation due to land use change threatens soil quality and watershed function in Java, Indonesia. This study aimed to evaluate soil quality across various land-use types in the Central Rembangan micro-watershed, East Java, Indonesia, using the Soil Quality Index (SQI) approach based on Principal Component Analysis (PCA). Soil samples were collected from 18 Land Mapping Units (LMUs). The LMU represents a combination of three types of land use, namely rice fields, plantations, and dryland agriculture. The LMU includes six slope classes, namely 0-3%, 3-8%, 8-15%, 15-25%, 25-40%, and >40%. The PCA analysis identified nine key indicators as the Minimum Data Set (MDS). These indicators include soil porosity, permeability, total nitrogen, exchangeable Mg, C/N ratio, soil pH, particle specific gravity, electrical conductivity (EC), and cation exchange capacity (CEC). The SQI value ranges from 0.50 to 0.77. The SQI value shows a significant difference between land use types at p<0.10. The rice field system has the highest SQI value of 0.68±0.09. The plantation system has an SQI value of 0.61±0.06. The dryland agricultural system has an SQI value of 0.57±0.09. Spatial analysis showed that 60% of micro-watershed areas have good soil quality. The good soil quality areas are located in the upstream part which is dominated by forest and plantations. As many as 40% of micro-watershed areas have moderate soil quality. Soil porosity and soil permeability are major contributors to soil quality in all types of land use.